Environmental Regulation and Labor Reallocation: Evidence from the Clean Air Act - Walker, W. Reed (American Economic Review, 2011)
This paper uses newly available data on plant level regulatory status linked to the Census Longitudinal Business Database to measure the impact of changes in county level environmental regulations on plant and sector employment levels. Estimates from a variety of specifications suggest a strong connection between changes in environmental regulatory stringency and both employment growth and levels in the affected sectors. The preferred estimates suggest that changes in county level regulatory status due to the 1990 Clean Air Act Amendments reduced the size of the regulated sector by as much as 15 percent in the 10 years following the changes.